The experience of mental effort during a continuous performance task: Exploring the influence of task- and person-based factors - Danika Wagner; John D. Eastwood (PLoS ONE, 2025)
Using mental effort to engage in cognitively demanding tasks is associated with a conscious experience, and this experience serves as a regulatory mechanism. However, important issues remain in our understanding and measurement of the experience of mental effort. For example, essential questions about how person- and task-based factors influence the experience remain unanswered. This study explored how the experience of task-elicited effort and volitionally exerted effort during a continuous performance task (CPT) are associated with person-based (i.e., trait inattention and hyperactivity) and task-based (i.e., manipulations in interstimulus intervals) factors. Participants reported levels of trait inattention and hyperactivity and were randomly assigned to one of three CPT ISI conditions (1000, 3000, or 6000 ms) and provided mid-task ratings of their experience of task-elicited and volitionally exerted mental effort. Both person- and task-based factors were associated with these distinct facets of the experience of mental effort. Several direct relationships exist between trait inattention and hyperactivity, mental effort components, and performance outcomes. However, only one of four moderated mediation models revealed a significant indirect effect: volitionally exerted brain power significantly mediated the relationship between trait inattention and hyperactivity and commission error rates, moderated by task condition with the strongest effect in the 6000 ms ISI. No moderated mediation effects emerged for task-elicited mental effort or latency outcomes. Recognizing that individual differences and task demands result in differing experiences of mental effort which, in turn, predict task performance, is an essential step in tailoring activities and interventions.